PENGARUH KEMAMPUAN GURU DAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA KELAS IV SD INPRES 01 PANIKI BAWAH - Supit, Patrisia Hana; Mandolang, Eunike; Walewangko, Stief Aristo; Tuwaidan, Virginia (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The ability of teachers and the use of learning media in learning at school can improve student learning outcomes. This research measures the influence of teacher abilities and the use of learning media on student learning outcomes (case study of all grade IV students at SD Inpres 01 Paniki Bawah). The problem in this research is what is the influence of teacher ability and use of learning media on the learning outcomes of grade 4 students at SD Inpres 01 Paniki Bawah? The aim of this research is to determine whether there is an influence of teacher ability and use of learning media on the learning outcomes of grade 4 students at SD Inpres 01 Paniki Bawah. This research approach is a quantitative approach. The population and sample in this study were 69 people who were obtained from the number of students in class IV of SD Inpres 01 Paniki Bawah. The data collection technique is carried out by distributing questionnaires. Data analysis uses simple and multiple linear regression analysis. The research results show that there is a significant influence between teacher ability and the use of learning media on student learning outcomes.